STUDI PERBANDINGAN KONSTITUSI TENTANG PENGATURAN IMPEACHMENT PRESIDEN NEGARA INDONESIA DAN JERMAN - Riyadi Eko Prasetyo; Zainal Arifin Hoesein (STKIP Subang, 2026)
Indonesia, as a state based on law, governs its affairs based on law or rechtstaat. Legal rules were created to prevent the growth of arbitrary power. This also applies to the presidential impeachment mechanism. The results show that the impeachment schemes between Indonesia and the Federal Republic of Germany share similarities. The Constitutional Court has the authority to adjudicate through the impeachment process. Although there are fundamental technical differences, the German Constitutional Court does not have a direct role in dismissing the Head of State but rather focuses on the constitutional review of laws. In Indonesia, the Constitutional Court is involved in the substantive verification of charges against the President and Vice President. From the perspective of the theory of the purpose of law, the Constitutional Court's position is as the guardian of the constitution and democracy, where impeachment of a head of state must be based purely on objectively proven errors, not politically motivated.